Oblicz ( to jest mnożenie z algebry)
a) -a (a + b)- 4(a + 3b) + 5 (4a - b) =
b) 6,5 (x - 2y) + 3/4 (4x - 2y) - 3 (0,5 - 1,5y) =
c) 4(2x - 3y - 5z) - 1/2 (6x - 12y - 8z)=
d) -2 [3(a - 2b) + 5 (2a - 3b)] - 4 (5a - 6b) =
e) 3[-2(x - 3y - 1) - (3 - 4y + x)] =
f) 3(x - 2y + 1) +4(2x - 3y + 4) - (3x - 7y + 2) =

3

Odpowiedzi

2010-04-11T17:49:26+02:00
A) -a(a+b)-4(a+3b)+5(4a-b)=-a2-ab-4a-12b+20a-5b=-a2+16a-ab-17b
b) 6,5 (x - 2y) + 3/4 (4x - 2y) - 3 (0,5 - 1,5y) =6,5x-13y+3x-1,5y-1,5+4,5y=9,5x-10y-1,5
c) 4(2x - 3y - 5z) - 1/2 (6x - 12y - 8z)=8x-12y-20z-3x+6y+4z=5x-6y-16z
d) -2 [3(a - 2b) + 5 (2a - 3b)] - 4 (5a - 6b) =-2[3a-6b+10a-15b]-20a+24b=-6a+12b-20a+30b-20a+24b=-46a+60b
e) 3[-2(x - 3y - 1) - (3 - 4y + x)] =3[-2x+6y+2]-3+4y-x]=-6x+18y+6-3+4y-x=-7x+22y+3
f) 3(x - 2y + 1) +4(2x - 3y + 4) - (3x - 7y + 2) =3x-6y+3+8x-12y+16-3x+7x-2=15x-18y+17
1 2 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-04-11T18:04:34+02:00
A) -a (a + b)- 4(a + 3b) + 5 (4a - b) =
=-2a-ab-4a-12b+20a-5b=
=12a-ab-17b

b) 6,5 (x - 2y) + 3/4 (4x - 2y) - 3 (0,5 - 1,5y) =
=6,5x-13y+3x-3/4y-1,5+4,5y =
=9,5x-7,75y-1,5

c) 4(2x - 3y - 5z) - 1/2 (6x - 12y - 8z)=
=8x-12y-20z-3x+6y+4z=
=5x-6y-16z

d) -2 [3(a - 2b) + 5 (2a - 3b)] - 4 (5a - 6b) =
=-2 [ 3a-6b+10a-15b] -20a+24b =
=-6a+12b-20a+30b-20a+24b=
=-46a+66b

e) 3[-2(x - 3y - 1) - (3 - 4y + x)] =
=3[-2x+6y+2-3+4y-x]=
=-6x+18y+6-9+4y-x=
=-7x+22y-3

f) 3(x - 2y + 1) +4(2x - 3y + 4) - (3x - 7y + 2) =
=3x-6y+3+8x-12y+16-3x+7y-2=
8x-11y+17
1 5 1
2010-04-11T18:10:02+02:00
A)=-(a do 2+ab)-(4a+12b)+(20a-5b)=-a do 2-ab-4a-12b+20a-5b=-a do 2 -ab+16a-17b
b)=6,5x-13y+3x-1,5y-1,5-4,5y=9,5x-19y-1,5
c)=8x-12y-20z-3x-6y-4z=5x-6y-16z
d)=2[(3a-6b)+(10a-15b)]-4(5a-6b)=2(13a-21b)-4(5a-6b)=26a-42b-20a-12b=6a-30b
e)=3(-2x+6y+2-3+4y-x)=-6x+18y+6-9+12y-3x=-9x+30y-3
f)= 3x-6y+3+8x-12y+16-3x+7y-2=8x-11y+17
1 5 1